TRANSLATION, CROSS-CULTURAL ADAPTATION AND VALIDATION OF POLYCYSTIC OVARIAN SYNDROME QUALITY OF LIFE SCALE IN PASHTO - Mahjabina S Ghayur,; Kareem, Rabia; Wahab, Samdana; Inayat, Sumaira; Karim, Rukhsana; Rauf Sethi, Mifrah; Nasr Malik, Naila; Irfan, Muhammad (Journal of Ayub Medical College Abbottabad, 2022)
Background: Cross-cultural adaptation and validation are important for the reliable use of a scale. This study was conducted to translate and validate the polycystic ovarian syndrome quality of life scale (PCOSQOL) in Pashto. Methods: This study was conducted in tertiary care teaching hospitals of Peshawar from August to December 2021 on 333 patients diagnosed with polycystic ovarian syndrome. Using forward-backward method, three bilingual experts translated PCOSQOL from English to Pashto. The exploratory and confirmatory factor analyses, Cronbach alpha reliability and construct validity of PCOSQOL (Pashto version) was found out using SPSS version 25 and AMOS version 26 for data analysis. Results: The mean age of the sample was 25.73±5.89 years. Majority were married (n=260, 78.1%), uneducated (n=180, 54.1%) and unemployed (n=303, 91%). Factorial validity of the Pashto version showed it to be a five-factor model. Regarding construct validity, the factor loading through Item total correlation scores revealed highly satisfactory correlation coefficients. The Cronbach's alpha reliability of the Pashto version of PCOSQOL was 0.918. The confirmatory factor analysis (CFA) indicated a good fit model with a CFI of 0.91 and a RMSEA value of .08. Poor quality of life (89.98±28.5) was reported in 169 (50.8%) women and this was irrespective of their educational and occupational background (p>0.05) respectively. Pearson coefficient correlation test showed a significantly positive Inter-scale correlation (p<0.05). Conclusion: Pashto version of PCOSQOL is a reliable instrument to measure the quality of life in patients with polycystic ovarian syndrome and can be used in Pashto speaking patients.